Unwound - James, Lorelei (James, Lorelei. Mastered series., 2014)
"When sensei Ronin Black first encounters Amery Hardwick, the fire in her eyes ignites a sexual spark a thousand times better than the primal rush he used to get from mixed martial arts matches. She accepts his darker edges and admits to him that her desires aren't as wholesome as he believed. And before long, Ronin is grappling with emotions he's never felt before.... Yet despite demanding Amery bare her body and soul to him, Ronin holds a part of himself back. When she learns Ronin's secret and walks out, his life begins to unravel. To regain her trust, he must let go of his pride and prove to her that it's more than passion binding them together. But after their private pleasures are made public, Ronin is unsure if he's the right man for Amery. Can they face the consequences together? Or will their differences rip them apart...?"--